2019
DOI: 10.1634/theoncologist.2019-0550
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Skin Reaction and Clinical Benefit in Patients Treated with Anti-Programmed Cell Death 1 Monotherapy for Advanced Non-Small Cell Lung Cancer

Abstract: Background Anti‐programmed cell death 1 antibody is a standard therapy for advanced non‐small cell lung cancer (NSCLC). However, immune‐related adverse events (irAEs), such as skin reactions, are frequently observed. Although skin reactions are associated with clinical efficacy in melanoma, this association in advanced NSCLC and predictors of irAEs remain unclear. Accordingly, this study identified potential correlations of skin reactions with clinical efficacy and clinical predictors of development of skin re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 38 publications
1
43
2
Order By: Relevance
“…In the present large-scale study involving 280 patients, we evaluated the association between irAEs and therapeutic effects, searched for predictive factors for the onset of irAEs and examined whether irAE profiles differ among cancer types. In this study, the overall incidence of treatment-associated adverse events was 41.1%, which was comparable with the previously reported incidence [5,8,9,12]. The most common adverse events were skin disorders.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In the present large-scale study involving 280 patients, we evaluated the association between irAEs and therapeutic effects, searched for predictive factors for the onset of irAEs and examined whether irAE profiles differ among cancer types. In this study, the overall incidence of treatment-associated adverse events was 41.1%, which was comparable with the previously reported incidence [5,8,9,12]. The most common adverse events were skin disorders.…”
Section: Discussionsupporting
confidence: 89%
“…irAEs attracted attention soon after the approval of ICIs, and since then, several reports have been published [5][6][7]. Although symptoms such as type 1 diabetes mellitus and severe diarrhoea had attracted attention, recent reports have indicated that the onset of irAEs contributes to the prognosis of patients [8][9][10][11][12][13]. However, many of the reports describe studies on malignant melanoma and lung cancer, for which ICIs were used ahead of the use for other cancers.…”
Section: Introductionmentioning
confidence: 99%
“…To account for the presence of lead-time bias associated with the time-dependent development of irAEs, we selected a 6-weeks study period in accordance with that in previous studies 10 , 11 . Another reason why the 6-week period was chosen was the occurrence rate of irAEs and the timing of computerized tomography.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that the presence of irAEs is associated with a higher efficacy and improved overall survival in several solid tumors treated with ICIs, including NSCLC ( 16 18 ). Nonetheless, ICIP might be an exemption to this rule.…”
Section: Discussionmentioning
confidence: 99%